Differences in Visual Perception Skills between Reading Disabilities and Low Achievement Primary Student in the Kingdom of Bahrain - Albannai, Zainab Ali (Journal of Educational and Psychological Sciences, 2023)
The main objective of this research is to find the differences in the visual perception between reading disabilities and low achievement primary student. By testing the modified visual perception skillsIn two dimensions; the visual discrimination and the visual memory. And their role in discovering students with reading disabilities as one of the most important cognitive abilities in the academic achievement. Which will help to identify this type of students and consider it as a learning disabilities. It will also help to determine the differences in the visual perception dimensions (the visual discrimination and the visual memory) and their impact on the level of academic achievement in students with reading disabilities and students with low achievement in Bahrain.The final research sample consisted of thirty four students devided into two groups; learning disabilities and low achievement.And the progressive matrices test, the Arabic class school grades records, diagnostic rating scale battery and the visual perception test were used as testing methods.Results have shown that there is no statistically significant differences in the visual discrimination from the scale of visual perception skills between students with reading disabilities and students with low achievement.They also have shown that there is no statistically significant differences in the visual memory from the scale of visual perception skills between students with reading disabilities and students with low achievement.
Keywords: Visual Perception; Reading Disabilities; Low Achievement